Монголын эртний улсуудын түүхийн үечлэлийн асуудалд - Дэлгэржаргал, Пүрэвсүрэн (Historia Mongolarum, 2008)
Монголын эртний улсуудын үечлэл болон Хүннү, Сяньбийн түүхийн үечлэлийг дахин нягтлан үзэж, үечлэлийн шинэ хувилбар санал дэвшүүлийг зорилоо. 842 - 923/924 оны үеийг “Монгол Татарын хаант улс”-ын үе гэж нэрлэх саналыг дэвшүүлж байгаа болно. The article describes the trends with which the Mongolians perceived their history during the modern period. In particular, the wake of the 1921 National Revolution brought an immense wave of nationalist interpretation of history, yet to be suppressed and supplanted by the official Marxist, anti""national in nature, historiography. It was only following the 1990 pro··democracy movement that nationalism was reintroduced as the core perception of history.